Pengaruh Persepsi Kepemimpinan Spiritual dan Komitmen Organisasi Terhadap Organization Citizenship Behavior (OCB) dengan Kepuasan Kerja Sebagai Variabel Intervening di PT.APF - Muhammad Amin; Arumwardani Nusandari; Rusmalia Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of perceptions of spiritual leadership and perceptions of organizational commitment on organizational citizenship behavior (OCB) with job satisfaction as an intervening variable at PT APF. This research was motivated by the gap between the initial questionnaire data which indicated a high level of organizational citizenship behavior (OCB), and the interview results which indicated the existence of employees with low organizational citizenship behavior (OCB). The research method used is quantitative, with data collection through questionnaires and interviews. The research sample was 112 employees of PT APF. Data analysis was carried out using multiple regression analysis with SmartPLS 4.0. The research results show that perceptions of : 1. Spiritual leadership influence organizational citizenship behavior (OCB). 2. Perceptions of organizational commitment influence organizational citizenship behavior (OCB). 3. Perceptions of spiritual leadership influence job satisfaction. 4. Perceptions of organizational commitment influence job satisfaction. 5. Job satisfaction influences organizational citizenship behavior (OCB). 6. Perceptions of spiritual leadership influence organizational citizenship behavior (OCB) through job satisfaction. 7. Perceptions of organizational commitment influence organizational citizenship behavior (OCB) through job satisfaction. The implication of this research is that it is important for companies to pay attention to spiritual leadership and organizational commitment to create a positive work environment to increase employee job satisfaction, which will ultimately have an impact on increasing employees' extra-role behavior.